2020
DOI: 10.1371/journal.pone.0241450
|View full text |Cite
|
Sign up to set email alerts
|

Extent of arterial calcification by conventional vitamin K antagonist treatment

Abstract: Background and aims Vitamin K antagonists (VKA) remain the most frequently prescribed oral anticoagulants worldwide despite the introduction of non-vitamin K antagonist oral anticoagulants (NOAC). VKA interfere with the regeneration of Vitamin K1 and K2, essential to the activation of coagulation factors and activation of matrix-Gla protein, a strong inhibitor of arterial calcifications. This study aimed to clarify whether VKA treatment was associated with the extent of coronary artery calcificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Vitamin K2 inhibition results in vascular calcification. 6 There is some concern that chronic use of VKAs can result in native valvular calcification. 7 If a similar phenomenon is seen in the prosthetic valves, it can be detrimental for their durability.…”
Section: Mechanisms Of Action For Coumadin and Direct Anticoagulantsmentioning
confidence: 99%
“…Vitamin K2 inhibition results in vascular calcification. 6 There is some concern that chronic use of VKAs can result in native valvular calcification. 7 If a similar phenomenon is seen in the prosthetic valves, it can be detrimental for their durability.…”
Section: Mechanisms Of Action For Coumadin and Direct Anticoagulantsmentioning
confidence: 99%
“…One of the largest studies was a retrospective cohort of 1748 warfarin users and 1148 DOAC users who had CT scans from 2007–2017. For each year of warfarin treatment, the odds of being in a higher coronary artery calcium (CAC) category increased (OR = 1.032, 95% CI 1.009–1.057), while DOAC treatment duration was not associated with CAC category (OR = 1.002, 95% CI 0.935–1.074) [ 62 ].…”
Section: Effects Of Warfarin Vs Doacs On Vascular Calcificationmentioning
confidence: 99%
“…Vitamin K antagonists (VKA), among the most recommended oral anticoagulants, influence the regeneration of vitamin K1 and K2, needed for the activation of coagulation factors and matrix Gla protein, which in turn is responsible for the inhibition of arterial calcification. The study conducted by Hasific et al, evaluating the relationship between VKA treatment and the extent of coronary artery calcifications, showed that a longer period of treatment with VKA, but not novel oral anticoagulants, was associated with the risk of a higher category of coronary artery calcification in patients without previous CVDs [ 124 ].…”
Section: The Contribution Of Dietary Factors To Vascular Calcificationmentioning
confidence: 99%